Carbon Dot Based Sensing of Dopamine and Ascorbic Acid. (29th December 2014) - Baruah, Upama; Gogoi, Neelam; Konwar, Achyut; Jyoti Deka, Manash; Chowdhury, Devasish; Majumdar, Gitanjali
Abstract : We demonstrate carbon dot based sensor of catecholamine, namely, dopamine and ascorbic acid. Carbon dots (CDs) were prepared from a green source: commercially available Assam tea. The carbon dots prepared from tea had particle sizes of ∼0.8 nm and are fluorescent. Fluorescence of the carbon dots was found to be quenched in the presence of dopamine and ascorbic acid with greater sensitivity for dopamine. The minimum detectable limits were determined to be 33  μ M and 98  μ M for dopamine and ascorbic acid, respectively. The quenching constants determined from Stern-Volmer plot were determined to be 5 × 10 −4 and 1 × 10 −4 for dopamine and ascorbic acid, respectively. A probable mechanism of quenching has been discussed in the paper.